Proposed use of TOGAF-Based Enterprise Architecture in Drinking Water Companies - Amanda, Djaja; Hindarto, Djarot; Indrajit, Eko; Dazki, Erick (Sinkron : jurnal dan penelitian teknik informatika, 2023)
The purpose of this research is to propose an enterprise architecture framework for planning a drinking water company blueprint. In drinking water companies, it is very important to ensure that the systems and information technology used meet business needs effectively and efficiently. However, the information system that supports the company's operations still needs to be improved, to get better operational quality. In this case, companies need a framework that can assist companies in designing and developing business architectures that strengthen competitive advantage, optimize operational performance, and ensure compliance with applicable regulations and standards. Therefore, the author proposes the selection of an enterprise architecture framework based on The Open Group Architecture Framework or TOGAF. The Open Group Architecture Framework is a widely used framework for developing and implementing enterprise architectures. TOGAF consists of four main components, namely business architecture, application architecture, technology architecture, and data architecture. Enterprise Architecture helps companies develop application and technology architectures that can accelerate product and service innovation and improve operational efficiency. Data architecture, managing and utilizing data effectively in making the right business decisions. By adopting the TOGAF-based Enterprise Architecture framework, water companies optimize the use of information systems and technology, increase flexibility in anticipating changes in community needs and accelerate innovation in products and services.